Clinical Profileof Patients having Acute Appendicitis: A Cross-Sectional Study - Asma Kafeel, Muhammad Abid Owais, Bushra Tasneem, Hassaan Hanif Khan, Aisha Tasneem, Samina Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To examine the clinical characteristics of patients with acute appendicitis Study design: A cross-sectional study Place and Duration: This study was conducted at Liaquat University Hospital Jamshoro / Hyderabad from March 2021 to March 2022. Methodology: Presentstudy included 118 patients who went through emergency appendectomy for acute appendicitis. The study evaluated the patient’s clinical profile who presented with acute appendicitis. A detailed history was taken, a clinical examination was performed, and tests such as a complete blood test and ultrasonography were performed. Patients of either gender, above 10 years of age, and with clinical diagnoses of acute appendicitis were incorporated in the study. Patients having an appendicular mass or right ureteric/renal colic were excluded from the study. Results: In the current study themean age of patients was 27.56 ± 9.8 years. Out of 118 patients, 71 (60.1%) were males, and 47 (39.83%) were females. We observed thepredominance of malesin the current study. Majority of the patients presented with complaints of right iliac fossa pain (98.3%) and migration of pain (67.8%). Nausea and anorexia were present in 86.4% of cases, and vomiting was present in 84.7% of cases.Tenderness was observed in right iliac fossa in all patients while Dunphy sign (59.3%), guarding (63.5%), rebound tenderness (69.4%), rigidity (5.9%), Psoas sign (45.7%), Rovsing sign (35.5%)and Obturator sign (21.1%). Conclusion: Males are more likely to have acute appendicitis than females between 10 and 30 years of age. The most common signs and symptoms were discomforts, anorexia, nausea/vomiting, and abdominal pain. Tenderness, guarding, and rebound tenderness were the most prevalent symptoms. Keywords: Appendicectomy, emergency department, Abdomen pain, Acute appendicitis